Post-stroke remodeling processes in animal models and humans. Issue 1 (January 2020) - Cirillo, Carla; Brihmat, Nabila; Castel-Lacanal, Evelyne; Le Friec, Alice; Barbieux-Guillot, Marianne; Raposo, Nicolas; Pariente, Jérémie; Viguier, Alain; Simonetta-Moreau, Marion; Albucher, Jean-François; Olivot, Jean-Marc; Desmoulin, Franck; et al.
After cerebral ischemia, events like neural plasticity and tissue reorganization intervene in lesioned and non-lesioned areas of the brain. These processes are tightly related to functional improvement and successful rehabilitation in patients. Plastic remodeling in the brain is associated with limited spontaneous functional recovery in patients. Improvement depends on the initial deficit, size, nature and localization of the infarction, together with the sex and age of the patient, all of them affecting the favorable outcome of reorganization and repair of damaged areas. A better understanding of cerebral plasticity is pivotal to design effective therapeutic strategies. Experimental models and clinical studies have fueled the current understanding of the cellular and molecular processes responsible for plastic remodeling. In this review, we describe the known mechanisms, in patients and animal models, underlying cerebral reorganization and contributing to functional recovery after ischemic stroke. We also discuss the manipulations and therapies that can stimulate neural plasticity. We finally explore a new topic in the field of ischemic stroke pathophysiology, namely the brain-gut axis.